The Effect of Using Memrise application on Students’ Vocabulary Mastery of The Seventh Grade at SMPS Prayatna Medan - Pasaribu, Siti Zubaidah; Sirait, Dahlia (Universitas Negeri Medan, 2023)
Many students have difficulty mastering vocabulary in English, including student have limited vocabulary and also having difficulty remembering unfamiliar vocabulary. The purpose of this research is to find out whether the Memrise application has an effect or not to mastering vocabulary. This research was conducted using quantitative methods. The research sample consisted of 20 students in class VII-1 as the experimental class and 20 students in class VII-2 as the control class. From the data that has been analyzed, the researcher found that the average result of the experimental class was 34 while the average result of the control class was 22. The results of calculations using the t test showed that t observed was higher than the t table (6.06 > 2.02) with df: 38 at the significance level a=0.025. So the alternative hypothesis (ha) is accepted and the null hypothesis is rejected. It can be concluded that the Memrise application in the vocabulary mastery learning process is effective to use.